In-vitro study of azadirachta indica and cymbopogon nardus leaf crude extracts against pyricularia oryzae a causal agent of blast disease on rice / Norsaleha Othman - Othman, Norsaleha (Faculty of Plantation and Agrotechnology, 2018)
Rice is a major source of food in the world. However, the production and quality of rice will affected because of rice disease. Blast is caused by the fungus Pyricularia oryzae and is the most important disease affecting rice in the world. The purpose of this study was to evaluate the potential of leaf extracts against the fungus that cause blast disease which is Pyricularia oryzae and to compare the effectiveness of two types of leaf extracts which is neem leaf (Azadirachta indica) and citronella grass (Cymbopogon nardus) with different concentration. The experiment conducted was using the poison food technique which is the PDA and different concentration (10%,20%,40% and 60%) of leaves extracts were mixed well. This method also used to evaluate the percentage of antifungal activity against the fungus. Completely Randomized Design (CRD) was implemented during the experiment sampling. The data was analysed by using Minitab software on One-Way ANOVA calculation method. The experiment outcome proportionally reflects to the objectives, both of leaf extracts has potential to against the growth of fungus P.oryzae by antifungal activity of extraction. Highest growth inhibition was achieved at 60% concentration with Citronella grass, 56.41% and neem leaves 39.32% mycelial growth inhibition. Extracts from A.indica and C.nardus at 60% concentration promoted significant (P≤0.05) inhibition on mycelial growth of P.oryzae than the control. However, leaves extracts of citronella grass at 60% was effective compared to 60% concentration of leaves extracts of neem. It could be inferred that extracts of A.indica and C.nardus at 60% concentration can serve as bio-fungicides against the growth of P.oryzae.